Scaffolding as Catalyst. - Cerf, Vinton G. (Communications of the ACM, 2023)
This article analyzes the concept of temporary scaffolding, taken from the construction industry, and applying it to internet development. Topics include the use of Arpanet as temporary scaffolding during the beginning of internet development, the use of the All-in-One Digital Equipment Corporation email service during development of the MCI Mail application, and use of temporary scaffolding in the development of the Solar System Internet during the process of testing the Bundle Protocol Suite. [EPC]